Pembinaan Petani Muda Desa dalam Pelatihan Penyusunan Inovasi Business Model Canvas dengan Menggunakan Design Thinking di Desa Kelungkung - Reza Muhammad Rizqi; Jayanti Mandasari; Sriyatun, Sriyatun (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The community service activity carried out with farmer groups in Kelungkung Village, Sumbawa Regency, aims to enhance farmers’ capacity and independence through an innovation-based business approach. The specific objectives of this activity include: (a) developing an innovation-oriented business model to support agricultural product enterprises, (b) strengthening marketing management for competitiveness, (c) improving skills in simple financial management analysis, and (d) providing an understanding of creative thinking methods capable of generating innovations by integrating community needs, technological potential, and business success factors. The methods applied involved training sessions, mentoring, and interactive discussions focusing on business model design, digital financial management practices, and modern marketing strategies. The results of the activity indicate that: (1) partners are able to understand and elaborate on key business components such as customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures; (2) partners can evaluate their businesses, identify opportunities, and formulate solutions to existing challenges; (3) partners have acquired basic knowledge of digital-based financial management analysis that is simple yet applicable; and (4) partners have developed the capacity to expand their farming enterprises, particularly in the field of digital marketing. Overall, this program has successfully encouraged farmer groups to be more adaptive to technological developments and modern market demands.